Green Religion, Science and Technology: Prospect and Challenge for Sustainable Life - Presenter of JIS (Joint International Seminar)
This International seminar is aimed to meet two elements, religious scholars and scientists, and to find out the same perspective between religious scholars and scientists in facing the challenges of global environmental crisis. The seminar is organized by Walisongo State Islamic University in cooperation with USIM Malaysia. The seminar covers several important topics such as: (1) Green religion: urgency, implementation, and implication (2) Green science: prospects and challenge (3) Green technology: review and progress (4 ) Common ground for go green: Concept and roadmap from three perspectives (religion, science, technology).